Kosheliuk Olena. Symbolization of mystic: psychoanalytical interpretation of the oniric text - Kosheliuk Olena (Philological Treatises, 2020)
The article deals with psychoanalytical interpretation of the dream images-symbols/ the main attention is on the archetype analysis as the way of investigation the poetic structure of the literary text. According to this methodic the archetypical images like Animus / Anima, Person / Shadow, Selfness are analyzed.